Failed Co-Creation: The Case of the BCNStreet-Lab Project - Vidal-Rojas, Juan-Carlos; Cereceda-Otárola, Marcos; Kourkoutas, Konstantinos; Roig-de-Zárate, Jordi; Vallrribera-Ros, Marc (Universidad Pedagógica y Tecnológica de Colombia, 2022)
We present the results of the BCNStreet-lab project, a co-creation process of a prototype that "died before it even existed" and that has led us to reflect on the creative power that participatory design can have among experts. Examining the high variability that the design acquired with the co-creation sessions, we realized how an open co-creation process can generate overflows in the design. It makes innovation possible but can also lead to failure, as is this case, because of how risky participatory design of “fluid technologies” and how ineffective reproducing the Quadruple helix innovation model in small projects can be. We tried to account for the fruitful relationship between co-creation and the design of electronic technologies, which happens in the “lobby” of the technical design of the prototype. It generates negotiations and interactions that lead to progress in the democratization of design practices in electronic engineering, computing, and telecommunications. At this point, co-creation is conceived as a space in which institutional practices, social needs, technological imaginaries, economic interests, techno-scientific interests, etc., are brought together, translated and inscribed into the design of technologies.